Religion in modern Islamic discourse - Tayob, Abdulkader (Columbia University Press, 2009)
[This book] examines the place of religion in debates and discussions from the nineteenth century to the present. Abdulkader Tayob follows the transformation of Islamic discourse, both in its adaptation and resistance to modernity. Tayob focuses on the efforts by intellectuals to reconcile Islam with the forces of modernization. He begins in Egypt and colonial India, closely reading works on the essence of religion and its social value. He then explores key contributions on identity, state, law, and gender.